2014
DOI: 10.1111/ppl.12201
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal coumaroyl anthocyanins protect sweet basil against excess light stress: multiple consequences of light attenuation

Abstract: The putative photoprotective role of foliar anthocyanins continues to attract heated debate. Strikingly different experimental set-ups coupled with a poor knowledge of anthocyanin identity have likely contributed to such disparate opinions. Here, the photosynthetic responses to 30 or 100% solar irradiance were compared in two cultivars of basil, the green-leafed Tigullio (TG) and the purple-leafed Red Rubin (RR). Coumaroyl anthocyanins in RR leaf epidermis significantly mitigated the effects of high light stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
102
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(116 citation statements)
references
References 89 publications
12
102
2
Order By: Relevance
“…Anthocyanin accumulation and coloration of fruits are affected by many cultivation practices, such as the use of reflective mulches or bagging, that may change the light environment within the tree canopy and around individual fruits (Ju et al 1999;Huang et al 2009;Overbeck et al 2013). The contents of flavonoids such as anthocyanin, catechins and flavonols increased in the leaves of Phillyrea latifolia and sweet potato during leaf exposure to sunlight or a long-day photoperiod (Carvalho et al 2010;Tattini et al 2014). We did not observe a red color in the leaves or calli under short-day conditions or in darkness.…”
Section: Discussionmentioning
confidence: 98%
“…Anthocyanin accumulation and coloration of fruits are affected by many cultivation practices, such as the use of reflective mulches or bagging, that may change the light environment within the tree canopy and around individual fruits (Ju et al 1999;Huang et al 2009;Overbeck et al 2013). The contents of flavonoids such as anthocyanin, catechins and flavonols increased in the leaves of Phillyrea latifolia and sweet potato during leaf exposure to sunlight or a long-day photoperiod (Carvalho et al 2010;Tattini et al 2014). We did not observe a red color in the leaves or calli under short-day conditions or in darkness.…”
Section: Discussionmentioning
confidence: 98%
“…Firstly, because anthocyanins originated from hydroxycinnamic acids and, as all the other flavonoids, they have evolved in more complexes chemical structures. Secondly, in addition to the protection against UV, especially due to acylation with phenolic acids (i.e., coumaric acid; Tattini et al, 2014), they serve as visible light filter as well as powerful antioxidants (Gould et al, 2009;Landi et al, 2015). Thus, anthocyanins exhibit properties of other different classes of molecules, but enclosed in a single one confirming the second criterion of the evolution: the efficiency of energy utilization.…”
Section: Anthocyanins As Part Of Plant Metal Homeostasis Network: Is mentioning
confidence: 90%
“…While there are six common anthocyanidins, there are more than 600 anthocyanins isolated from plants , 277 of which have been identified after 1992 (Andersen and Jordheim, 2006). In view of the chemical structure of anthocyanins and their histological localization, different protective functions have been hypothesized even though, concerning plant protection against abiotic stress, photoprotection from high light and UV-B (Agati et al, 2007;Tattini et al, 2014) and ROS scavenging ability are the most widely postulated as stress reliever (Gould et al, 2002;Kytridis and Manetas, 2006). On the other hand, defence against herbivores and attraction of pollinators (or preys in carnivorous plants) are the most proposed functions for anthocyanins in terms of relationships with biotic factors (Gould et al, 2009;Hughes and Lev-Yadun, 2015;Menzies et al, 2015).…”
Section: The Key Role Of Phenols In Terrestrial Plants Evolutionmentioning
confidence: 99%
“…Because acylated anthocyanins are not as common as the non-acylated forms, their UV-absorbing functions are unlikely to be a universal primary role for anthocyanins in planta (Hatier and Gould, 2009). However, only a few studies on photo-abatement have fully identified the chemical structure of individual anthocyanins inside the leaf (Burger and Edwards, 1996;Andersen et al, 2010;Tattini et al, 2014), and acylated anthocyanins may be more abundant in leaves than has been previously assumed. It is perhaps surprising that in most studies anthocyanins are quantified only spectrophotometrically by measuring the absorbance of the total pool.…”
Section: Anthocyanins As Sunlight Attenuators And/or Ros-scavengersmentioning
confidence: 92%
“…The common anthocyanin glycosides have negligible molar absorption coefficients in the UV region (Woodall and Stewart, 1998;Agati and Tattini, 2010), but after acylation with phenolic acids, anthocyanins may contribute substantially to UV protection ( Fig. 3; Takahashi et al, 1991;Burger and Edwards, 1996;Tattini et al, 2014). Because acylated anthocyanins are not as common as the non-acylated forms, their UV-absorbing functions are unlikely to be a universal primary role for anthocyanins in planta (Hatier and Gould, 2009).…”
Section: Anthocyanins As Sunlight Attenuators And/or Ros-scavengersmentioning
confidence: 93%